2002
DOI: 10.1016/s0375-9474(02)01187-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-pion production in proton–proton collisions near threshold

Abstract: Two-pion production reactions in proton-proton collisions have been studied using the PROMICE/WASA detector and an internal cluster gas-jet target at the CELSIUS storage ring in Uppsala. Three out of the four isospin-independent reaction channels have been measured at several energies in the intermediate and near threshold energy region. Important p a r t s o f the analysis include the identi cation of neutral pions from the invariant mass of the decay gammas, the identi cation of positive pions with the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…As a result of these kinematically complete and exclusive two-pion production measurements at CELSIUS and subsequently at COSY it was shown that all pp induced, i.e. all isovector channels, behave as expected from conventional t-channel excitation of Roper, ∆∆ (mutual excitation of the colliding nucleons into their first excited state ∆(1232)) and ∆(1600) resonances [8,9,10,11,12,13,14,15,16,17].…”
Section: Exclusive and Kinematically Complete Experiments -Observatiomentioning
confidence: 88%
“…As a result of these kinematically complete and exclusive two-pion production measurements at CELSIUS and subsequently at COSY it was shown that all pp induced, i.e. all isovector channels, behave as expected from conventional t-channel excitation of Roper, ∆∆ (mutual excitation of the colliding nucleons into their first excited state ∆(1232)) and ∆(1600) resonances [8,9,10,11,12,13,14,15,16,17].…”
Section: Exclusive and Kinematically Complete Experiments -Observatiomentioning
confidence: 88%
“…Starting first with the WASA/PROMICE detector setup, followed by the completed WASA detector at CELSIUS and finally at COSY all ppinduced, i.e. isovector two-pion production channels from threshold up to √ s = 2.5 GeV have been studied [323,324,325,326,327,328,329,330,331] complemented by a corresponding program with polarized beam at COSY-TOF [314,332]. The results for the total cross sections are shown in Fig.…”
Section: No Dibaryon Signal In Pp-induced Two-pion Productionmentioning
confidence: 99%
“…As a result it was found [350] that there is, indeed, a highly visible low-mass enhancement but no high-mass enhancement as seen in previous σ 0 π + π pn → pp Figure 9: Energy dependence of the pp-induced total cross sections for two-pion production and their isospin decomposition. Open symbols denote results from bubble-chamber measurements [317,318,319,320,321,322], solid symbols represent measurements from WASA/PROMICE (triangles) [323,324,325], CELSIUS/WASA (circles) [326,327,328,329,330] and COSY-TOF (squares) [314]. At the top the reaction channels pp → ppπ 0 π 0 (left) and pp → nnπ + π + (right) are shown together with their isospin decomposition.…”
Section: Following a Trace: The Abc Effectmentioning
confidence: 99%
“…Overall, the process scrutinized here corresponds on the target side to a nn → pp + ππreaction. In free space, the corresponding charge-conjugated reaction pp → nn + π + π + reaction and other double-pion production channels were in fact already investigated experimentally at CELSIUS and COSY [153], [154], [155], [156], [157], [158], [159], [160], [161], [162], [163] and later also at HADES [164]. Thus these correlations are expected to be present also in more involved nuclear reactions.…”
Section: Analogy Between Dce Reactions and 0νββ Decaymentioning
confidence: 96%